THE EFFECT OF PROFITABILITY, LEVERAGE, INSTITUTIONAL OWNERSHIP COMPANY SIZE AND GENDER DIVERSITY OF THE BOARD OF COMMISSIONERS ON CORPORATE SOCIAL RESPONSIBILITY (CSR) DISCLOSURE - Bambang Sugiharto; Indah Umiyati; Winda Nuraini (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2023)
The purpose of this study was to determine whether there is an effect of profitability, leverage, firm size, institutional ownership and gender diversity of the board of commissioners on the disclosure of Corporate Social Responsibility (CSR). In this study, various industrial companies have been listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The data analysis method used is panel data regression analysis with the EVIEWS 9 program. Then the sample used in this study was 24 companies using non-probability sampling technique and using purposive sampling method in determining the sample criteria that have been set in this study. The results showed that partially the variables of firm size and institutional ownership had a significant positive effect on the disclosure of corporate social responsibility, while the profitability and gender diversity of the board of commissioners had a significant negative effect on the disclosure of corporate social responsibility. Then Leverage has no effect on the disclosure of corporate social responsibility. And the results of the study also show that simultaneously the variables of profitability, leverage, firm size, institutional ownership and gender diversity of the board of commissioners affect the disclosure of corporate social responsibility (CSR).